The role of conspiracy mindset in reducing support for child vaccination for COVID-19 in the United States - Romer, Daniel; Jamieson, Kathleen H. (Frontiers in Psychology, 2023)
We have previously proposed and tested a model that predicts reluctance to vaccinate against COVID-19 in the US from embrace of a conspiracy mindset that distrusts federal health agencies of the US government and regards itheir intentions as malevolent. In this study, we tested the model’s ability to predict adult support for COVID vaccination of children ages 5-11 after the vaccine was approved for this age group. Relying on a national panel that was established in April 2021 (N=1941) and followed until March of 2022, we examined the relation between conspiratorial thinking measured at baseline and belief in misinformation and conspiracies about COVID-19 vaccines, trust in various health authorities, perceived risk of COVID to children, and belief in conspiracy theories about the pandemic’s origin and impact. In addition, we tested a structural equation model (SEM) in which conspiracy mindset predicted adult support for childhood vaccination for COVID in January and March of 2022 as well the adults’ own vaccination status and their willingness to recommend vaccinating children against measles, mumps and rubella (MMR). The model accounted for 76% of the variance in support for childhood vaccination for COVID; the relation between the mindset and support for vaccination was entirely mediated by baseline assessments of misinformation, trust, risk, and acceptance of pandemic conspiracy theories. The SEM replicated the prior test of the model, indicating that a conspiracy mindset present among at least 17% of the panel underlies their resistance to vaccinate both themselves and children. Efforts to counteract the mindset will likely require the intervention of trusted spokespersons who can overcome the skepticism inherent in conspiratorial thinking about the government and its health-related agencies' recommendations for a particular vaccine.